Transcriptomic Profiling Reveals the Antiapoptosis and Antioxidant Stress Effects of Fos in Ischemic Stroke - Mu, Qiancheng; Zhang, Yuxuan; Gu, Long; Gerner, Stefan T.; Qiu, Xiancheng; Tao, Qianke; Pang, Jinwei; Dipritu, Ghosh; Zhang, Lifang; Yin, Shigang; Jiang, Yong; Peng, Jianhua (Frontiers in Neurology, 2021)
Arterial hypertension is considered the most prevalent risk factor for stroke. Both pathophysiologic and clinical data previously acquired suggest a strong correlation between the hemodynamic nature of arterial hypertension and an increase in the risk of ischemic insult to tissues. However, the knowledge of specific molecular interactions between hypertension and ischemic stroke (IS) is limited. In this study, we performed systematic bioinformatics analysis of stroke-prone spontaneous hypertensive brain tissue samples of rats (GSE41452), middle cerebral artery occlusion of brain tissue samples of rats (GSE97537), and peripheral blood array data of IS patients (GSE22255). We identified that Fos, an immediate-early gene (IEG) that responds to alterations in arterial blood pressure, has a strong correlation with the occurrence and prognosis of IS. To further evaluate the potential function of Fos, the oxygen–glucose deprivation model and RNA sequencing of HT22 neuronal cells were performed. Consistent with the sequencing results, real-time quantitative PCR and Western blot indicate that Fos was elevated at 3 h and returned to normal levels at 6 h after oxygen–glucose deprivation. Knock-down of Fos by lentivirus significantly increased the oxidative stress level, neuronal apoptosis, and inhibited the mitochondrial function. In conclusion, Fos acts as an important link between hypertension and IS. Furthermore, Fos can be used as a potential biomarker for target therapy in the prevention of stroke among hypertensive patients and also potential treatment targeting apoptosis and oxidative stress after its onset.